IMPLEMENTASI PEMBELAJARAN SAINS AUD MELALUI PERMAINAN TERAPUNG DAN TENGGELAM - Munawaroh, Hidayatu (Kopertais Wilayah X Jawa Tengah, 2017)
The research is motivated by scientiÃ« c learning which was given by the teacher wasless attractive, monotonous, even using the manufactured game and toy that tendedÂ Â to be practically. The purpose of this research is to know how the scientiÃ« c learningÂ implementation through Ã¬ oat and sink game in learning. The type of the research is descriptive research which uses qualitative approach. The result of the research is aboutÂ the given scientiÃ« c learning by the teacher has adjusted with the theme and the subÂ theme, the method which is used by the teacher in scientiÃ« c learning has been able toÂ develop the scientiÃ« c ability of children such as using experiment method. The obstacleÂ is the teachersâ creativeness in designing scientiÃ« c activity.